Understanding and exploiting long-lived near-infrared emission of a molecular ruby - Otto, Sven; Dorn, Matthias; Förster, Christoph; Bauer, Matthias; Seitz, Michael; Heinze, Katja (Coordination Chemistry Reviews)
Keywords: Materials Chemistry; Physical and Theoretical Chemistry; Inorganic Chemistry

Structure–function relationship during CO2 methanation over Rh/Al2O3 and Rh/SiO2 catalysts under atmospheric pressure conditions - Martin, Natalia M.; Hemmingsson, Felix; Wang, Xueting; Merte, Lindsay R.; Hejral, Uta; Gustafson, Johan; Skoglundh, Magnus; Meira, Debora Motta; Dippel, Ann-Christin; Gutowski, Olof; Bauer, Matthias; Carlsson, Per-Anders (Catalysis Science & Technology)
Intermediate species formed during CO2 methanation over Rh/Al2O3 and Rh/SiO2 catalysts.
Keywords: Catalysis

A Straightforward Synthesis to Novel 1,10-Phenanthrolines with Fused Thiophene Structure - Bauer, Matthias; Tünnermann, Maike; Rehsies, Pia; Flörke, Ulrich (Synlett)
We report here a straightforward synthesis for a series of new structures with fused 1,10-phenanthroline-thiophene connection. They are synthesized with a modified Hinsberg thiophene procedure, followed by successive modification to yield several 5,7-disubstituted thieno[3,4-f][1,10]phenanthrolines, most notable thiophene-substituted compounds that could be potentially of use for organic electronics applications. For some selected examples, crystal structures were obtained, showing a nearly coplanar arrangement around the fused connection, also beneficial for an effective electron transfer in organic electronics or solar cells.
Keywords: Organic Chemistry

The Bonding Situation in the Dinuclear Tetra-Hydrido Complex [{5CpFe}2(μ-H)4] Revisited by Hard X-Ray Spectroscopy - Burkhardt, Lukas; Mueller, Carsten; Groß, Oliver A.; Sun, Yu; Sitzmann, Helmut; Bauer, Matthias (Inorganic Chemistry)
Keywords: Inorganic Chemistry; Physical and Theoretical Chemistry

Entwicklung und Synthese von Ein- und Mehrkomponentensystemen zur photokatalytischen Wasserreduktion - Meinhardt, Regina

A Novel Lubricant Based on Covalent Functionalized Graphene Oxide Quantum Dots - Wolk, Andreas; Rosenthal, Marta; Neuhaus, Stephan; Huber, Klaus; Brassat, Katharina; Lindner, Jörg K. N.; Grothe, Richard; Grundmeier, Guido; Bremser, Wolfgang; Wilhelm, René (Scientific Reports)

Effect of ionic strength on the structure and elongational kinetics of vimentin filaments - G. Lopez, Carlos; Saldanha, Oliva; Aufderhorst-Roberts, Anders; Martinez-Torres, Cristina; Kuijs, Merel; Koenderink, Gijsje H.; Köster, Sarah; Huber, Klaus (Soft Matter)
The present work characterizes the assembly process of vimentin intermediate filaments with monovalent salts as an assembly trigger. A multi-scale approach is used, comprising time-resolved static and dynamic light scattering and quantitative scanning transmission electron microscopy.
Keywords: Condensed Matter Physics; General Chemistry

Liquid-liquid phase separation in dilute solutions of poly(styrene sulfonate) with multivalent cations: Phase diagrams, chain morphology, and impact of temperature - Hansch, Markus; Hämisch, Benjamin; Schweins, Ralf; Prévost, Sylvain; Huber, Klaus (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Polyacrylates in the presence of an extraordinary monovalent cation—Solution behavior and metal nanoparticle formation - Urbanski, Anna; Hansch, Markus; Lopez, Carlos G.; Schweins, Ralf; Hertle, Yvonne; Hellweg, Thomas; Polzer, Frank; Huber, Klaus (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Insight into Fast Nucleation and Growth of Zeolitic Imidazolate Framework-71 by In Situ Static Light Scattering at Variable Temperature and Kinetic Modeling - Saha, Sanjib; Wiebcke, Michael; Huber, Klaus (Crystal Growth & Design)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Reaction enthalpy from the binding of multivalent cations to anionic polyelectrolytes in dilute solutions - Hansch, Markus; Kaub, Hans Peter; Deck, Sascha; Carl, Nico; Huber, Klaus (The Journal of Chemical Physics)
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Secondary Particle Formation during the Nonaqueous Synthesis of Metal Oxide Nanocrystals - Stolzenburg, Pierre; Hämisch, Benjamin; Richter, Sebastian; Huber, Klaus; Garnweitner, Georg (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Selective pore filling of mesoporous CMK-5 carbon studied by XRD: Comparison between theoretical simulations and experimental results - Weinberger, Christian; Hartmann, Marc; Ren, Sai; Sandberg, Thomas; Smått, Jan-Henrik; Tiemann, Michael (Microporous and Mesoporous Materials)
It is possible to infiltrate a guest species selectively in one pore system of bimodal mesoporous CMK-5 carbon by an optimized nanocasting procedure. The selective filling has a drastic impact on the low-angle X-ray diffraction pattern of this novel class of materials. The structures of CMK-5, CMK-5 composite materials (sulfur and SnO2 as guest species), and CMK-3 carbon were simulated to investigate the influence of the pore filling with different guest species on the diffraction pattern and compared with experimental results. Additionally, the impact of structural defects is taken into account. The nature of the guest species strongly influences the relative intensity of the diffraction peaks. It turns out that the diffraction patterns of sulfur-carbon composite materials are nearly identical as those of CMK-3 carbon, which is attributed to a similar electron density of carbon and sulfur. Thus, sulfur is an ideal guest species to investigate the selective pore filling in CMK-5 carbon.

Porous Aluminum Oxide and Magnesium Oxide Films Using Organic Hydrogels as Structure Matrices - Chen, Zimei; Kuckling, Dirk; Tiemann, Michael (Nanomaterials)
We describe the synthesis of mesoporous Al2O3 and MgO layers on silicon wafer substrates by using poly(dimethylacrylamide) hydrogels as porogenic matrices. Hydrogel films are prepared by spreading the polymer through spin-coating, followed by photo-cross-linking and anchoring to the substrate surface. The metal oxides are obtained by swelling the hydrogels in the respective metal nitrate solutions and subsequent thermal conversion. Combustion of the hydrogel results in mesoporous metal oxide layers with thicknesses in the μm range and high specific surface areas up to 558 m2∙g−1. Materials are characterized by SEM, FIB ablation, EDX, and Kr physisorption porosimetry.

Bimodal Mesoporous CMK-5 Carbon: Selective Pore Filling with Sulfur and SnO2 for Lithium Battery Electrodes - Weinberger, Christian; Ren, Sai; Hartmann, Marc; Wagner, Thorsten; Karaman, Didem. Ş.; Rosenholm, Jessica M.; Tiemann, Michael (ACS Applied Nano Materials)
Ordered mesoporous CMK-5 carbon exhibits two distinct pore systems that can be modified individually. This work demonstrates how one of the pore systems can be selectively filled with elemental sulfur, while the other pore system remains empty. The resulting sulfur–carbon composite material with high residual porosity can be used as the cathode material in lithium–sulfur battery cells. We present a systematic investigation of the loading of CMK-5 carbon with variable relative amounts of sulfur and compare the results to the preparation of SnO2 (as well as TiO2, Mn2O3/Mn3O4, NiO) nanoparticle-loaded CMK-5 carbon.

Hydrogels as Porogens for Nanoporous Inorganic Materials - Weinberger, Christian; Kuckling, Dirk; Tiemann, Michael (Gels)
Organic polymer-hydrogels are known to be capable of directing the nucleation and growth of inorganic materials, such as silica, metal oxides, apatite or metal chalcogenides. This approach can be exploited in the synthesis of materials that exhibit defined nanoporosity. When the organic polymer-based hydrogel is incorporated in the inorganic product, a composite is formed from which the organic component may be selectively removed, yielding nanopores in the inorganic product. Such porogenic impact resembles the concept of using soft or hard templates for porous materials. This micro-review provides a survey of select examples from the literature.

Impact of finite-temperature and condensed-phase effects on theoretical X-ray absorption spectra of transition metal complexes - Müller, Patrick; Karhan, Kristof; Krack, Matthias; Gerstmann, Uwe; Schmidt, Wolf Gero; Bauer, Matthias; Kühne, Thomas D. (Journal of Computational Chemistry)

Nanoscopic Structures and Molecular Interactions Leading to a Dystectic and two Eutectic Points in [EMIm][Cl] / Urea Mixtures - Cerajewski, U.; Träger, J.; Henkel, S.; Roos, A. H.; Brehm, Martin; Hinderberger, D. (Phys. Chem. Chem. Phys.)

Structure and Lifetimes in Ionic Liquids and their Mixtures - Gehrke, S.; von Domaros, M.; Clark, R.; Hollóczki, O.; Brehm, Martin; Welton, T.; Luzar, A.; Kirchner, B. (Faraday Discuss.)

Salt Bridge in Aqueous Solution: Strong Structural Motifs but Weak Enthalpic Effects - Pylaeva, S.; Brehm, Martin; Sebastiani, D. (Sci. Rep.)